2011
DOI: 10.1242/jcs.085407
|View full text |Cite
|
Sign up to set email alerts
|

Linking cytoplasmic dynein and transport of Rab8 vesicles to the midbody during cytokinesis by the doublecortin domain-containing 5 protein

Abstract: SummaryCompletion of mitosis requires microtubule-dependent transport of membranes to the midbody. Here, we identified a role in cytokinesis for doublecortin domain-containing protein 5 (DCDC5), a member of the doublecortin protein superfamily. DCDC5 is a microtubuleassociated protein expressed in both specific and dynamic fashions during mitosis. We show that DCDC5 interacts with cytoplasmic dynein and Rab8 (also known as Ras-related protein Rab-8A), as well as with the Rab8 nucleotide exchange factor Rabin8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 75 publications
(72 reference statements)
2
27
0
Order By: Relevance
“…Additionally, recently published work also suggested that Rab5, Rab6, Rab8a, Rab21 and Rab24 may also play a role in cytokineis, although their exact function remains to be fully understood. [47][48][49][50][51] What, if any, function do these Rab GTPases play during cytokinesis remains to be determined and will require further studies. Additionally, very little is known about the involvement of Rabs and endocytic membrane transport in regulating specialized and assymetric types of cytokinesis and abscission.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recently published work also suggested that Rab5, Rab6, Rab8a, Rab21 and Rab24 may also play a role in cytokineis, although their exact function remains to be fully understood. [47][48][49][50][51] What, if any, function do these Rab GTPases play during cytokinesis remains to be determined and will require further studies. Additionally, very little is known about the involvement of Rabs and endocytic membrane transport in regulating specialized and assymetric types of cytokinesis and abscission.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has been demonstrated to direct polarized trafficking events during ciliogenesis, neuronal development, regulated secretion and cytokinesis (Yoshimura et al, 2007;Nachury et al, 2007;Huber et al, 1995;Chen et al, 2001;Kaplan and Reiner, 2011), possibly through the ability to reorganize actin and microtubules (Peränen et al, 1996). Defects in Rab8 function have been implicated in trafficking diseases, including retinal degeneration, cell polarity defects and irregular tissue formation (Moritz et al, 2001;Satoh et al, 2007;Huber et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…During cytokinesis, MICAL3 directly interacts with the centralspindlin component MKLP1 (also known as KIF23) and recruits the adaptor protein ELKS (also known as ERC1), which tethers Rab8A-positive vesicles to the midbody . Importantly, Rab8A vesicles are known to transport important molecules, which are yet to be identified, that promote late cytokinetic steps (Guizetti et al, 2011;Kaplan and Reiner, 2011;Schiel et al, 2012). As a consequence, the depletion of either ELKS or Rab8A leads to abscission defects.…”
Section: Activation Of Mical1mentioning
confidence: 99%